Impact of wave–current coupling on the bottom boundary layer in Bohai Bay - Liu, Siyu; Li, Guangxue; Liu, Xue; Qiao, Lulu; Wang, Nan; Liu, Shidong; Wang, Xiangdong; Yu, Di; Zhang, Lei (Frontiers in Marine Science, 2025)
Sediment resuspension primarily occurs within the bottom boundary layer (BBL) of water bodies, particularly in silty coastal environments, and helps form the fluid mud layer (FML). In this study, we report data on the water level, waves, currents, and suspended sediment concentration (SSC) collected from the Bohai Sea over one year, at a vertical resolution of 4 cm, by using the acoustic wave and current profiler, acoustic Doppler current profiler, and an acoustic backscattering system. The aim was to investigate the mechanisms of formation and disappearance of the FML as driven by wave–current interactions on silty seabeds The findings revealed a thin and stable FML within 4–12 cm of the seabed in shallow waters. Strong waves contributed more significantly to sediment resuspension than strong currents. Moreover, the SSC near the seabed was generally governed by the currents, while waves were predominant in this regard in stormy conditions. The index of intensity of the bottom shear β—defined as the ratio of the wave–current-induced shear stress to the critical shear stress—was identified as a sensitive indicator of variations in the SSC. Significant sediment resuspension occurred in case of the coupling of large wave and current events on the fine-grained seabed, when the value of β exceeded 10 for more than 20 h and the Rouse number persisted below 0.01 for over 30 h. Following the storm (β < 10), the sediment gradually accumulated, and this led to the formation of the FML. Prolonged periods in which the value of β surpassed 10 for over 10 h while that of the Rouse number remained below 0.01 for more than 30 h resulted in considerable sediment resuspension and the destruction of the FML. Our results highlight the profound impacts of wave–current interactions on the formation and disappearance of the FML within the BBL in silty, shallow marine environments. The work here offers critical insights into the dynamics of fine-particle sediment, and provides suggestions for mitigating the negative effects associated with the FML.